2009
DOI: 10.1093/sleep/32.5.623
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence and Persistence in Severe Obstructive Sleep Apnea

Abstract: Medication adherence and persistence during a 2-year period for 3 well-known protective cardiovascular medications were not different in patients with severe OSA, whether or not they were treated with CPAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 32 publications
4
28
1
3
Order By: Relevance
“…They found no difference in the rates of medication adherence between the two groups, suggesting that nonadherence to CPAP does not necessarily imply nonadherence to pharmacotherapy. Th e present fi ndings are in line with Villar et al 42 and reinforce the notion that untreated moderate-severe OSA may be an independent risk factor for repeat revascularization aft er PCI. Another limitation was that CPAP adherence was based on subjective patient report rather than on objective adherence data obtained from the CPAP devices.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They found no difference in the rates of medication adherence between the two groups, suggesting that nonadherence to CPAP does not necessarily imply nonadherence to pharmacotherapy. Th e present fi ndings are in line with Villar et al 42 and reinforce the notion that untreated moderate-severe OSA may be an independent risk factor for repeat revascularization aft er PCI. Another limitation was that CPAP adherence was based on subjective patient report rather than on objective adherence data obtained from the CPAP devices.…”
Section: Discussionsupporting
confidence: 92%
“…Th e strategy of reviewing pharmacy records for prescription refi lls as a marker of medication adherence has been well described in the cardiovascular literature. 41 Villar et al 42 examined adherence to cardiovascular medications (ie, antihypertensive, lipid-lowering, and antiplatelet drugs) in two groups of patients with severe OSA and cardiovascular disease: those who were adherent to CPAP treatment and those who refused treatment or were nonadherent to CPAP. They found no difference in the rates of medication adherence between the two groups, suggesting that nonadherence to CPAP does not necessarily imply nonadherence to pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, these differences cannot be statistically confirmed because of the time‐dependent study design and absence of independent observations, though the observed differences seem substantial. Adherence to medical treatment in patients with SA has been investigated in a cohort of 2158 patients with severe OSA; in this study the authors found high medication adherence among all patients and, remarkably, no difference in medication adherence between patients adherent and nonadherent to CPAP therapy 27. This supports our findings of CPAP therapy possibly playing an active role in reducing the risk of developing HF in SA patients.…”
Section: Discussionsupporting
confidence: 85%
“…It is reported that patients not accepting CPAP have the same high compliance with drugs for elevated cholesterol, for reducing hypertension, etc. 44 We conclude that CPAP treatment is associated with lower mortality rates in males with OSA, including the middle-aged and elderly (aged $60 years). However, we found no significant effect on all-cause mortality of CPAP treatment in female OSA patients.…”
Section: Discussionmentioning
confidence: 70%